2004
DOI: 10.1097/00005176-200401000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Zinc With Oral Rehydration Therapy Reduces Stool Output and Duration of Diarrhea in Hospitalized Children: A Randomized Controlled Trial

Abstract: This study demonstrates a beneficial effect of zinc administered during acute diarrhea on stool output, diarrheal duration, and proportion of episodes lasting more than 7 days. The effects are large enough to merit routine use of zinc during acute diarrhea in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 21 publications
3
89
0
1
Order By: Relevance
“…Study characteristics are shown in Table 1 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Only three studies had a population of fewer than 100 patients, and all studies were conducted in countries considered to be "emerging and developing economies" (48).…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics are shown in Table 1 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Only three studies had a population of fewer than 100 patients, and all studies were conducted in countries considered to be "emerging and developing economies" (48).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that zinc, in conjunction with ORS, is effective in reducing acute diarrhea by 15%-25%; however, its mechanism of action is uncertain (152,153). Oral zinc can correct a common micronutrient deficiency in children with diarrhea (154).…”
Section: Scientific Challenges That Remainmentioning
confidence: 99%
“…The effect of probiotics in management of acute diarrhea have been postulated and understood to be because of mechanism like immonological tolerance, producing bacterocins to act as local antibiotics, inhibiting pathogen growth by luminal pH, improving mucosal integrity by stimulating mucin production and by decreasing potent proinflammatory cytokines and enhancing the production of antiinflammatory cytokines. [2][3][4] In a published summary of 73 studies of children who sought care for diarrhea in 33 countries Rotavirus was the most frequently identified. 5,6 Optimal management of diarrhea patients including choice of therapy differs in invasive and noninvasive diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Management of acute non bloody diarrhea includes fluids & supportive care in form of Zinc. 2,4 The management in the form of giving probiotics has long been advocated. Probiotics are by definition of WHO and FAO of United Nations are living microorganism which when administered in adequate amount confer a health benefit to the host.…”
Section: Introductionmentioning
confidence: 99%